1998
DOI: 10.1093/jat/22.5.383
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Metabolites of Nerve Agent VX in Serum Collected from a Victim

Abstract: A human serum sample collected from a victim of the Osaka VX incident was analyzed according to our developed technique for metabolites of VX. Gas chromatography-mass spectrometry (GC-MS) in full-scan electron impact and chemical ionization modes were used, and, for more reliable confirmation, GC-MS-MS was also employed. In the serum sample, both ethyl methylphosphonic acid and 2-(diisopropylamino-ethyl)methyl sulfide were detected. These results indicated that the techniques using GC-MS and GC-MS-MS were appl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
55
1
4

Year Published

2000
2000
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(61 citation statements)
references
References 18 publications
0
55
1
4
Order By: Relevance
“…The main metabolite of VX nerve agent, respectively ethyl methylphoshonate (EMPA) was detected as TBDMS ester by GC/MS and GC/MS/MS analysis, in the serum sample of the person killed by VX [9,14]. A concentration of 1250 ng/ml was estimated in the blood sample collected after one hour from the occurrence of the assassination and stored for several months at −20 °C.…”
Section: Detection In Cases Of Human Poisoningmentioning
confidence: 99%
“…The main metabolite of VX nerve agent, respectively ethyl methylphoshonate (EMPA) was detected as TBDMS ester by GC/MS and GC/MS/MS analysis, in the serum sample of the person killed by VX [9,14]. A concentration of 1250 ng/ml was estimated in the blood sample collected after one hour from the occurrence of the assassination and stored for several months at −20 °C.…”
Section: Detection In Cases Of Human Poisoningmentioning
confidence: 99%
“…After intravenous and dermal administration of sublethal doses of VX to swine, both VX and EA2192 could be quantified during 540 min after exposure (Reiter et al, 2011). In addition, there are two nonphosphorus metabolites of VX: DAET and its methylation product DAEMS identified in human serum from a victim of the Osaka VX accident (Tsuchihashi et al, 1998). The conversion from DAET to DAEMS is catalyzed by thiol S-methyltransferase (EC 2.1.1.9) (Reiter et al, 2011).…”
Section: Chemical Aspects Of Biotransformation Of Wnasmentioning
confidence: 99%
“…In vitro studies with 35 S-VX revealed that a significant part of the thiol-containing leaving group (S-2-(N, N-diisopropylamino)ethane thiol) was bound to albumin. Tsuchihashi et al (1998) developed a method for identification of VX metabolites in serum collected from a victim of the Osaka VX incident. In the serum sample, both EMPA and DAEMS were detected.…”
Section: Chemical Aspects Of Biotransformation Of Wnasmentioning
confidence: 99%
“…GC-MS methods based on silylation were adapted for the analysis of biomedical samples associated with the Matsumoto and Tokyo terrorist incidents, e.g. [62,63]. Lowest detection limits are achieved with pentafluorobenzyl esters, in combination with negative ion chemical ionisation (NICI) GC-MS-MS, e.g.…”
Section: Gc-ms(-ms) Analysismentioning
confidence: 99%